PENGARUH PENDEKATAN MODIFICATION OF RECIPROCAL TEACHING PADA MATERI REDOKS TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA KELAS X SMA KOPERASI PONTIANAK - Retno Anjar Kusuma; Tuti Kurniati; Rizmahardian Azhari Kurniawan (Jurnal Ilmiah Ar-Razi, 2018)
The background of this research was the lack of students’ learning activities in the classroom and the low of student learning outcomes in the oxidation reduction material. This research aimed to determine whether there are any differences in the activities and learning outcomes of students who were taught using modification of reciprocal teaching approach and students who were taught using the expository approach and how much the influence of modification of reciprocal teaching approach to the activities and student learning outcomes. This research used experimental method with nonequivalent control group design. Samples were selected using saturation sampling technique. Data collection techniques used were measurement, observation and direct communication techniques. Data collection tools used were learning result test, observation sheet and interview guide. Based on the results of statistical analysis using SPSS 22.0, it can be concluded that there were differences in activity and student learning outcomes students who were taught using modification of reciprocal teaching approach and expository approach. The value of effect size showed that the effect of 92.07% approach to student learning activities and 99.20% of student learning outcomes. So it can be concluded that the modification of reciprocal teaching approach can be used to improve student activity and learning outcomes.Keywords: Learning activities, Learning outcomes, Modification of Reciprocal Teaching, Redox